Behaviour of lightweight beam using EPS beads as partial replacement of aggregates - Muhammad Farhan, Soed (2016)
Reinforced concrete is compulsory in nowadays building and they contain cement, aggregates, steel then mix with the water. The purpose of this mixture is sometimes different according what to be built. Fresh concrete can built into any shape and they are good in compression but weak in tension. The main objective of this study is to determine compressive strength and the cracking pattern of lightweight concrete to be used as normal beam by using polystyrene beads. The tests has been conducted to find compressive strength and the deflection of the beam. All the procedures are prepared accordingly, to assure the research objectives are applicable, and to secure proper sequence and smooth running of the entire flow, from start until end. Six samples had been prepapred, which two of them are ratio control, ratio and ratio 2 significantly. All six samples of the reinforced beam are concreted at Heavy Structure Laboratory, University Malaysia Pahang (UMP) and compressive strength test also conducted at same laboratory. The result that had been received are likely like the theory means that the ratio control will have the highest load compare the other two ratios. As conclusion, EPS can be used as extenuating agent in concrete. However, from the observation, we can hardly distinguish which of normal beam is stronger. Besides that, the development of the graph pattern for each sample is not consistent, thus explains the indifferences of the load bearing capacity.